2016
DOI: 10.1038/srep28159
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Free Fatty Acid Receptor 2 leads to impaired islet mass and beta cell survival

Abstract: The regulation of pancreatic β cell mass is a critical factor to help maintain normoglycemia during insulin resistance. Nutrient-sensing G protein-coupled receptors (GPCR) contribute to aspects of β cell function, including regulation of β cell mass. Nutrients such as free fatty acids (FFAs) contribute to precise regulation of β cell mass by signaling through cognate GPCRs, and considerable evidence suggests that circulating FFAs promote β cell expansion by direct and indirect mechanisms. Free Fatty Acid Recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 52 publications
2
50
0
1
Order By: Relevance
“…Thus, it has been reported that a phenylacetamide derivative agonist of FFAR2 enhances β-cell proliferation, 14 FFAR2 knockout mice show reduced β-cell expansion during pregnancy, 27 and a FFAR2 agonist that preferentially couples via Gq promotes mouse islet β-cell proliferation. 28 Consistent with SCFAs playing an important role in maintaining β-cell mass, we have In summary, we have demonstrated that increasing colonic propionate improves β-cell function in vivo, and our in vitro observations in human islets indicate that this may occur both via short-term acute effects of propionate to directly stimulate insulin secretion and through its longer-term effects to protect β-cells from apoptotic stimuli. These data support the ingestion of propiogenic dietary fibres to maintain healthy glucose homeostasis, both through the established beneficial effects via elevations in GLP-1 and PYY 16 and by the novel signalling identified here, of direct stimulatory effects of propionate at β-cells.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, it has been reported that a phenylacetamide derivative agonist of FFAR2 enhances β-cell proliferation, 14 FFAR2 knockout mice show reduced β-cell expansion during pregnancy, 27 and a FFAR2 agonist that preferentially couples via Gq promotes mouse islet β-cell proliferation. 28 Consistent with SCFAs playing an important role in maintaining β-cell mass, we have In summary, we have demonstrated that increasing colonic propionate improves β-cell function in vivo, and our in vitro observations in human islets indicate that this may occur both via short-term acute effects of propionate to directly stimulate insulin secretion and through its longer-term effects to protect β-cells from apoptotic stimuli. These data support the ingestion of propiogenic dietary fibres to maintain healthy glucose homeostasis, both through the established beneficial effects via elevations in GLP-1 and PYY 16 and by the novel signalling identified here, of direct stimulatory effects of propionate at β-cells.…”
Section: Discussionsupporting
confidence: 80%
“…Recent studies in mice have indicated direct signalling via FFAR2 in islets to regulate β‐cell mass. Thus, it has been reported that a phenylacetamide derivative agonist of FFAR2 enhances β‐cell proliferation, FFAR2 knockout mice show reduced β‐cell expansion during pregnancy, and a FFAR2 agonist that preferentially couples via Gq promotes mouse islet β‐cell proliferation . Consistent with SCFAs playing an important role in maintaining β‐cell mass, we have demonstrated, for the first time, that propionate significantly reduced human islet apoptosis induced by sodium palmitate and by cytokines.…”
Section: Discussionsupporting
confidence: 77%
“…Although FFAR2 and FFAR3 deletion is reported to improve glucose tolerance in obese mice, it has also been reported that FFAR2 −/− mice fed a high‐fat diet show no changes in glucose tolerance and that obese and pregnant FFAR2 −/− mice develop glucose intolerance, so it is not clear from published studies whether FFAR2 improves or impairs glucose homeostasis. The observation that FFAR2 −/− mice have reduced β‐cell mass at birth suggests a role for FFAR2 in β‐cell development, and the reduced β‐cell area was also observed in adulthood . However, β‐cell proliferation is elevated in FFAR2 −/− mice and deletion of FFAR2 does not impair glucose tolerance in mice fed normal chow, suggesting that FFAR2 is not essential for normal glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we and others have identified that FFAR2 and FFAR3 are expressed by islets of Langerhans, opening up the possibility that SCFAs contribute to the regulation of insulin secretion through activation of these receptors. However, the data published so far do not provide a consensus role for SCFAs and their receptors in islets: the first paper published in this area reported that acetate inhibited insulin release in vitro and that deletion of FFAR2 and FFAR3 improved glucose tolerance, while there have been more recent reports of SCFAs stimulating insulin secretion and of deletion of FFAR2 being associated with insufficient β‐cell mass expansion in obesity and gestational diabetes . Acetate is the most abundant circulating SCFA, reaching plasma concentrations of ~200 μM, while propionate concentrations are ~10‐fold lower, and these are the two SCFAs that are used most commonly for experimental studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation